INVO Procedure: Minimally Invasive IVF as an Alternative Treatment Option for Infertile Couples - Elkin Lucena; Angela M. Saa; Doris E. Navarro; Carlos Pulido; Oscar Lombana; Abby Moran (The Scientific World Journal)
Intravaginal culture (IVC), also called INVO (intravaginal culture of oocytes), is an assisted reproduction procedure where oocyte fertilization and early embryo development are carried out within a gas permeable air-free plastic device, placed into the maternal vaginal cavity for incubation. In the present study we assessed the outcome of the INVO procedure, using the recently designed INVOcell device, in combination with a mild ovarian stimulation protocol. A total of 125 cycles were performed. On average 6.5 oocytes per cycle were retrieved, and a mean of 4.2 were placed per INVOcell device. The cleavage rate obtained after the INVO culture was 63%. The procedure yielded 40%, 31.2%, and 24% of clinical pregnancy, live birth, and single live birth rates per cycle, respectively. Our results suggest that the INVO procedure is an effective alternative treatment option in assisted reproduction that shows comparable results to those reported for existing IVF techniques.